(untitled) (Transport systems and technologies, 2018)
The goal of the robots is to obtain the values of coefficient of decision (Kp) and plot a histogram of the probability distribution of these values for the selected type of maneuver. In the article the method of modeling the driver’s behavior at non-adjustable intersections in intersecting flows is investigated. Analysis and processing of video recording of the motion of intersecting streams at the quadrilateral crossroads of the city of Kharkov, chosen by street road network (SRN), is performed. An improved method of "boundary intervals" is proposed as a "sliding boundary interval" for modeling the driver’s behavior. As a result of processing the video recording of the flow of streams at unregulated intersections, a histogram of the probability distribution of the values of the decisiveness coefficient for crossing flows was constructed [11, 12]. With the help of such histograms, the Kp values for each car in the stream can be specified using any known random number generator. This method will take into account both the individual characteristics of drivers and the impact on their behavior of objective factors, the proposed method of recording drivers in modeling the movement of traffic flows will increase the accuracy of modeling, which in turn will allow us to refine a number of results that we obtain by modeling, for example, the calculation of the throughput of lanes. The proposed method of simulating the driver’s behavior in the models of traffic flows makes it possible to approximate the accuracy of simulation to the real variety of behavior of drivers, and, consequently, to increase the adequacy of models.